The gobioid fishes of India—An annotated list - Larson, Helen K.; Murugan, A. (Zootaxa, 2026)
The gobioid fishes of India have been misidentified and misunderstood for many years; there are over 250 nominal species recorded so far, plus many for which we were unable to confirm identity or presence in India. A look at much of the Indian literature on these fishes shows a confusion of names, with some species being endemic, some species widespread, and many misidentified. The taxonomy of many Indo-Pacific gobioid genera and species is still not understood. The rise of social media and citizen science is assisting in documenting these fishes, but much work remains to be done. Increased collaboration and access to Indian material is needed.